Soil Structure Interaction of Underpass RCC Bridge - Prof. Swapnil Cholekar, Vinayak Demane (International Journal of Scientific Research and Management (IJSRM), 2013)
The Underpass RCC Bridge is very rarely adopted in bridge construction but recently the Underpass RCCBridge is being used for traffic movement. Hence constructing Underpass Bridge is a better option where thereis a constraint of space or land. The bridges are structure, which provides means of communication over a gap.Bridges provided passage for vehicular or other type of traffic. The model is analyzed for bending moment, shear force and axial thrust for different loading combinations asper IRC: 6-2010 standards. As the box structure directly rests on soil and also soil pressure acts at the sidewalls. It is important to study the soil structure interaction of such structure. To study the response of structurewith rigid supports, with soil structure interaction applied to base only results.and with soil structureinteraction applied to base and side walls of the structure and comparing the